Precision Medicine in Overlap Syndrome (COPD–Obstructive Sleep Apnea): From Phenotypes and Endotypes to Treatable Traits - Carina Adina Afloarei; Andreea Zabara Antal; David Toma; Adriana Loredana Pintilie; Georgiana Pitusac; Raluca Tiron; Tudor Birladeanu; Teodor Zaharia; Radu Crisan Dabija (Advances in Respiratory Medicine, 2026)
Introduction: COPD-OSA overlap syndrome (OVS) is defined by the coexistence of chronic obstructive pulmonary disease and obstructive sleep apnea syndrome in the same patient; it affects 28.3% of patients evaluated for either condition and is associated with significantly higher mortality compared to either pathology in isolation. Current therapeutic approaches, involving PAP therapy and bronchodilation, treat this syndrome as a homogeneous entity and ignore the biological heterogeneity of this patient population. Objectives: This review proposes a systematic framework for the endotypic classification of biological interactions between COPD and OSA, integrating current literature on the pathophysiological mechanisms underlying the OVS, clinically accessible biomarkers, and emerging therapies. Methods: A narrative review based on available literature, focusing on studies published between 2010 and 2026 identified via searches in PubMed, PMC, and Dove Medical Press using the terms: COPD-OSA overlap syndrome, endotype, precision medicine, phenotype, biomarker, dupilumab, and incretin-based therapies. Results: Four clinical phenotypes (obese-metabolic, emphysematous, bronchitic-hypoxemic, and hypercapnic) and three molecular endotypes (Th2/eosinophilic, neutrophilic/oxidative, and metabolic-adipokine) are proposed, each with distinct pathophysiological mechanisms and specific therapeutic implications. The interaction between the two conditions generates a unique, pronounced hypoxemic profile. We propose the “double-hit hypoxemia” model as a conceptual framework characterized by amplified systemic inflammation and increased cardiovascular risk compared to either pathology in isolation. This proposed model has not yet been prospectively validated. Dupilumab (approved for an inflammatory phenotype in COPD patients characterized by eosinophil counts ≥ 300 cells/μL) represents a promising option, though currently unsupported in the OVS population, that could nonetheless be relevant to the Th2/eosinophilic endotype of this syndrome and tirzepatide (which reduced the AHI by up to 23.8 events/hour versus placebo in the SURMOUNT-OSA trial, conducted in patients with obesity and moderate-to-severe OSA, rather than in patients with confirmed OVS) could represent a promising therapy for the metabolic-adipokine endotype of obese patients with OVS. A minimal biomarker panel, comprising blood eosinophils, FeNO, daytime PaCO2, BMI, and T90, allows for a practical approach to identifying the dominant endotype. Conclusions: Endotyping of OVS may provide a framework for moving beyond a uniform therapeutic approach toward more individualized management based on the dominant underlying biological mechanism. Randomized clinical trials focusing on endotypic stratification and OVS cohorts remain research priorities.